Helsinki Study of Religions: A Reader - Holm, Nils G. (Uskonnontutkija - Religionsforskaren, 2016)
Bokrecension av Riku Hämäläinen, Heikki Pesonen & Terhi Utriainen (eds.) 2016. Helsinki Study of Religions. A Reader. Uskontotiede 17. Helsingfors universitet, 492 sidor.